A Comparison of the state-favored religions in Turkey and Hungary - Yilmaz Fadime (RELIGION AND SOCIETY IN CENTRAL AND EASTERN EUROPE, 2022)
Is it possible to establish a radical separation between religion and politics in constitutionally secular states? Is religion a private or political matter? In many countries, religious people are becoming activists, involving politics, trying to change the policies based on their beliefs or get a share of the state power. Their claims sometimes fall within the democratic structure of the country, and sometimes outside of it. This paper provides insight into the relation between state and religion by focusing on the religious politics of two countries, Turkey and Hungary This study is, in essence, a crossregional and cross-religious comparative study, presenting the very first comparison of the state-religion relationships in the two countries. Ninian Smart’s concept of dimensions of religion will be used as a framework to extract a pattern for each country. These dimensions exist in social systems and reflect the cultural and social milieu in which people socialize and build their own beliefs. Our goal is to present and prove that the religious features of Turkey and Hungary are comparable and show similarities along each dimension of Smart. Exploratory qualitative analysis will be employed to collect and analyze qualitative data in order to generate new concepts and generalizations. The data will be collected from open sources, such as newspapers, statistics, and survey results in Hungary and Turkey, to find the answer to the research questions. The main results of our comparative analysis are, first, evidence for substantial similarities regarding the presence of religion in the public sphere in each Smartian dimension, although in countries that are very different in terms of religion. Second, our systematic and structured analysis provides a strong and impartial invitation for further comparative research from both qualitative and quantitative perspectives. This study is going to provide data collected from open sources such as newspapers, statistics, survey results in Hungary and Turkey, in order to find the reply to these questions.